DIGITAL DENTISTRY: COMPUTER EQUIPMENT IN THE SERVICE OF MEDICINE - Abdurashidov Oybekjon Abdurashid ugli (Sciental Journals Publishing, 2025)
Digital dentistry is a dental treatment technology that uses computer systems and equipment. Today, this area is actively developing, and new-generation clinics are beginning to use modern devices. Computer scanning is used at the diagnostic stage, as well as for creating dental casts, modeling, and prosthetics. CAD/CAM techniques are being especially actively implemented.